Islam Di Eropa: Mendayung Di Antara Debat dan Negosiasi - M. Amin Nurdin (ILMU USHULUDDIN, 2018)
For 30 years the practice of multicultural ideology is a ‘success story’ in European migrant countries in managing multicultural societies, but in the last 10 years there has been a very heated debate among governments, politicians, and people who consider that this ideology has failed to unite (integration) immigrants, especially Muslim minorities in the mainstream of European way of life. The debate was triggered by the rise of the radical Islamic movement marked by the events of September 11, 2001 at the WTC New York, the bombing at the London Railway Station on July 7, 2005, a caricature of insulting Prophet Muhammad in Charlie Hebdo magazine in France, the Brussels case in 2016, terrorist attacks in Germany, and so on. The ideological failure factor is considered not only rooted in Western countries’ fear of the rise of militant groups that discredit the practice of multiculturalism, but also fosters Huntington’s thesis on the ‘clash of civilizations’ between Islam and the West. Islamic civilization is considered as an internal enemy against Western civilization (internal enemy). Whether we realize it or not, the above theory has a social political impact. This thesis has become a seed for the growth of the institutionalization of Islamophobia in the midst of society aimed directly at Muslims. To answer the above fear, the question arises, whether the application of the multiculturalism ideology will continue or return to the old concept of ‘monoculturaslime’ which is racist and conservative? In this case there are two opinions between rejecting and agreeing that need to be negotiated, in addition to the Muslims themselves seeking a form of Islam that is in accordance with European values (Euro-Islamic Norm) as is the case with the Archipelago Islam in Indonesia.